GODAN, a vanguard global partnership - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2015)
In the era of open data, agriculture and nutrition are starting to push forward. Indeed, in this as in so many other sectors, free access to high quality data is of vital importance. The Global Open Data for Agriculture and Nutrition (GODAN) Initiative, which held its first conference in January 2015 in the Netherlands has demonstrated this